Spontaneous Poisoning by Sprouts of Xanthium spp. in Cattle in Southern Rio Grande do Sul - Alberti, Taina dos Santos; Zamboni, Rosimeri; Scheid, Haide Valeska; Venancio, Fabiano da Rosa; Brunner, Carolina Buss; Raffi, Margarida Buss; Schild, Ana Lucia; Sallis, Eliza Simone Viégas (Acta Scientiae Veterinariae, 2020)
Background: Xanthium spp., the cockleburs, are invasive plants found on riverbanks, lakeshores, and floodplains. Ingestion of Xanthium sprouts or fruit causes cocklebur toxicosis, which is characterized clinically and pathologically by acute liver failure. The main lesion observed is an accentuation of the lobular pattern of the liver (nutmeg appearance), which is microscopically characterized by coagulation necrosis in the centrilobular region, hepatocyte degeneration in other regions of the hepatic parenchyma, and sinusoidal congestion. The objective of this study was to describe an outbreak of spontaneous cattle poisoning by ingestion of Xanthium spp. sprouts in the southern region of Rio Grande do Sul, Brazil. Case: In September 2018, a beef cattle farm located in Rio Grande county, Rio Grande do Sul, Brazil, reported significant mortality of cattle in a short period of time. There were 700 cattle on the property, divided by class into three different herds, all kept under extensive conditions in native wetlands. All fields were heavily infested by cocklebur, with most plants in the budding stage. Twenty animals developed muscle tremors, salivation, aggression, and recumbency. The clinical course lasted 24 to 48 hours, with a lethal outcome in all cases. An 18-month-old male crossbreed bovine was sent to the Regional Diagnostic Laboratory of the Universidade Federal de Pelotas (UFPel) School of Veterinary Medicine for necropsy. Gross examination revealed ascites and accentuation of the lobular pattern of the liver. Organ fragments were harvested and fixed in 10% buffered formalin. Microscopically, the liver exhibited marked coagulation necrosis in the centrilobular region and vacuolization of the hepatocyte cytoplasm in the midzonal and periportal regions. In the brain, there was perineuronal edema, cytoplasmic shrinkage and basophilia, gliosis, and satellitosis. Discussion: In the present case, the diagnosis of cocklebur toxicosis was based on clinical and epidemiological data as well as macroscopic and microscopic histopathology findings, and was confirmed by the presence of Xanthium spp. in the grazing sites of the affected animals. The detection and identification of Xanthium spp. are essential for correct etiologic diagnosis, since the pathological lesions observed in cocklebur toxicosis are similar to those described in poisoning by other hepatotoxic plants (Cestrum parqui, Cestrum corymbosum, Cestrum intermedium, Dodonea viscosa, Trema micranta) and by Perreya flavipes larvae. Central nervous system (CNS) symptoms were the main clinical manifestation observed in this outbreak, and the CNS lesions observed on necropsy were similar to those described in previous cases of cocklebur toxicosis. The predominance of nervous signs in this condition often misdirects the clinical diagnosis toward diseases such as rabies and cerebral babesiosis, which are endemic in southern Rio Grande do Sul and important causes of mortality in cattle herds. In these cases, careful attention to epidemiology, necropsy findings, and histopathology are fundamental for establishing the definitive diagnosis of cocklebur toxicosis and thus preventing further cases from being missed. The description of this outbreak emphasizes the importance of cocklebur toxicosis as an underreported cause of acute mortality in cattle in southern Brazil.